Prevalence of cytogenetic anomalies in couples with recurrent miscarriages: A Case-control study - Vishali Kalotra; Meena Lall; Pushpa Saviour; Ishwar Chander Verma; Anupam Kaur (Wolters Kluwer Medknow Publications, 2017)
Background: About 15%-20% of couples get affected by recurrent miscarriages (RM) and chromosomal abnormality in one partner affects 3%-6% of RM couples. Aims: The present study aimed to determine the prevalence of cytogenetic anomalies in couples with RM. Settings and Design: A case-control study was undertaken, in which 243 couples who had experienced 2 or >2 miscarriages were investigated for chromosomal abnormalities and compared with 208 healthy, age-matched control couples who had at least one healthy live born and no history of miscarriages. Material and Methods: Peripheral blood (PB) lymphocytes were cultured using PB-Max Karyotyping medium (GIBCO) for chromosomal analysis and 20 metaphases were analyzed for each individual. Statistical Analysis: Student's t-test was used for statistical evaluation and P < 0.05 was considered statistically significant for all instances. Results: The current study revealed 3.1% RM cases showing structural chromosomal aberrations, of which balanced translocations and Robertsonian translocations constituted 66.7% and 26.7% cases, respectively, while inversions constituted 6.7% abnormal RM cases. Polymorphic variations were observed in 1.9% RM patients and 1.2% controls as well. However, the number of abortions were significantly more (P = 0.027) in male carriers of balanced translocations as compared to female carriers in the RM group. There was no significant difference for age (P = 0.539) between RM women and control women. Conclusions: Although similar studies exist in literature, our study is the first of its kind from our region that has compared the chromosomal anomalies between the RM group and the control group. We observed 3.1% of balanced translocations and an increased number (though nonsignificant) of polymorphic variations and satellite associations in the RM group as compared to the control group.